Changes in the expression of meteorin‐like (METRNL), irisin (FNDC5), and uncoupling proteins (UCPs) after bariatric surgery. Issue 8 (18th July 2022) - Jamal, Mohammad H.; AlOtaibi, Fatemah; Dsouza, Carol; Al‐Sabah, Suleiman; Al‐Khaledi, Ghanim; Al‐Ali, Waleed; Ali, Hamad; Cherian, Preethi; Al‐Khairi, Irina; Devarajan, Sriraman; Abu‐Farha, Mohamed; Al‐Mulla, Fahd; et al.
Abtract: Objective: Bariatric surgery is currently the most effective treatment for severe obesity. This study aims to investigate the changes in expression levels of meteorin‐like protein (METRNL), irisin (FNDC5), and uncoupling proteins (UCP) 1/2/3 following bariatric surgery to understand their involvement in enhancing metabolism after surgery. Method: A total of 40 participants were enrolled in this interventional study, 20 with obesity BMI ≥ 35 kg/m 2 and 20 with BMI ≤ 25 kg/m 2 . Bariatric surgery (laparoscopic sleeve gastrectomy and Roux‐en‐Y gastric bypass) was performed. The levels of various molecules of interest were analyzed before and after surgery. Results: Gene expression analysis revealed significantly higher levels of METRNL, UCP1, and UCP3 in individuals with obesity when compared with healthy individuals before surgery ( p < 0.05). Gene expression levels of METRNL and UCP2 showed a significant increase after bariatric surgery ( p < 0.05). METRNL plasma level was significantly higher in individuals with obesity before surgery (mean [SEM], 55, 222.6 [1, 421.1] pg/mL, p = 0.0319), as well as at 6 and 12 months (57, 537.3 [1, 303.9] pg/mL, p = 0.0005; 59, 334.9 [1, 214.3] pg/mL, p < 0.0001) after surgery. Conclusion: The changes in the levels of various molecules of interest support their possible involvement in the inflammatory and thermogenic responses following bariatric surgery.